Microscopic Enteritis; clinical features and correlations with symptoms - Shahraki, Touran (Research Institute for Gastroenterology and Liver Diseases, 2012)
AIM: To assess the clinical characteristic of CD as well as correlation of symptoms and the degrees of intestinal mucosal lesions in Iranian children. BACKGROUND: Microscopic Enteritis (Marsh 0-II) is associated with malabsorption. PATIENTS AND METHODS: From August 2005 to September 2009, 111 cases with malabsorption and classical gastrointestinal symptoms were evaluated. RESULTS: The mean (±SD) age of children with CD was 4.9±3.5 years (range, 6 month - 16 years) and the mean duration of symptoms was 8 ± 20.5 months. 50 cases (45%) were female and 61 cases (55%) were male. The most common clinical presentation was failure to thrive in 72%, chronic diarrhea in 65.8% and Iron deficiency anemia in 59.5%. Sensitivity of EMA was 100% in patients with Marsh IIIb and Marsh IIIc. EMA was also positive in 77% of cases with Marsh 0, 18% in Marsh I, 44% in Marsh II and 81.8% in patients with Marsh IIIa. CONCLUSION: Histopathology did not reflect the severity of gluten sensitivity. This would suggest that the degree of intestinal mucosal damage might not be a reliable prognostic factor. Significant symptoms can be present with minor histological change on biopsy.